Ergasiophytes of Seymskyi Regional Landscape Park (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
Ergasiophytes of Seymskyi Regional Landscape Park (Sumy Oblast, Ukraine) have been studied. The species composition of the group area established. Ergasiophytes are represented by 100 species from 90 genera and 40 families of vascular plants. Their systematic and biomorphological structure have been analyzed. Asteraceae, Rosaceae, Fabaceae, Poaceae, Solanaceae, Cucurbitaceae, Brassicaceae, Juglandaceae and Vitaceae are dominant families. Phanerophytes (42; 42%) predominate among life forms; therophytes (29; 29%) and hemicryptophytes (25; 25%) are represented by a smaller number of species. All species, with the exception of Secale cereale (archaeophyte), are classified as kenophytes according to the time of introduction. Species of North American origin significantly predominate (33; 33%), Asian species (13; 13%), in particular, East Asian (7; 7%) and Mediterranean (12; 12%) are significantly less common. The largest group is colonophytes (29; 29%) by the degree of naturalization, the following positions occupied by ephemerophytes (22; 22%), agrio-epoecophytes and ergasiophygophytes – 15 species each (15%). The stable component of the flora of the park is 63%. Acer negundo, Robinia pseudoacacia and Solidago canadensis are xeno-ergasiophytes with an invasive status in the region and are dangerous for the phytobiota of the studied area. Potentially invasive species that have a tendency to naturalize in natural habitats and dominate in plant communities are identified: Asclepias syriaca, Parthenocissus inserta, Rudbeckia hirta, Amorpha fruticosa, Lupinus polyphyllus, Heliopsis scabra. The participation of the above-mentioned species in different types of habitats analyzed and maps of their distribution in the park were compiled for further monitoring. The beginning of introduction of species that have few localities in the territory of the park, but tend to run wild near the places of introduction with subsequent distribution, was noted: Thladiantha dubia, Silphium perfoliatum, Helianthus tuberosus, Hemerocallis fulva, Rosa rugosa, Caragana arborescens.
Keywords: introduced species, escaped plants, Sumy region.